2017
DOI: 10.1039/c7tb00481h
|View full text |Cite
|
Sign up to set email alerts
|

Effective co-delivery of nutlin-3a and p53 genes via core–shell microparticles for disruption of MDM2–p53 interaction and reactivation of p53 in hepatocellular carcinoma

Abstract: Using core–shell microparticles encapsulating p53/β-CD-g-CS NPs and nutlin-3a effectively suppressed p53–MDM2 interaction and restored p53 apoptotic activity in cancer cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 56 publications
0
10
0
Order By: Relevance
“…Another valuable advantage of electrohydrodynamic techniques is how they enable the encapsulation of bioactive elements with distinct chemical structures, including not only small molecules but also DNA [ 290 , 291 ] and proteins [ 285 , 292 , 293 ]. Cell electrospinning has also been performed, allowing the direct incorporation of live cells during the scaffold manufacturing process [ 294 ].…”
Section: Osteochondral Tissue Engineeringmentioning
confidence: 99%
See 1 more Smart Citation
“…Another valuable advantage of electrohydrodynamic techniques is how they enable the encapsulation of bioactive elements with distinct chemical structures, including not only small molecules but also DNA [ 290 , 291 ] and proteins [ 285 , 292 , 293 ]. Cell electrospinning has also been performed, allowing the direct incorporation of live cells during the scaffold manufacturing process [ 294 ].…”
Section: Osteochondral Tissue Engineeringmentioning
confidence: 99%
“…Importantly, all scaffolds supported hBMSC attachment and proliferation, as well as ECM production and expression of chondrogenic genes (type II collagen, Sox9, aggrecan, and proteoglycan 4 (PRG4)), particularly KGN-loaded fibres [289]. Another valuable advantage of electrohydrodynamic techniques is how they enable the encapsulation of bioactive elements with distinct chemical structures, including not only small molecules but also DNA [290,291] and proteins [285,292,293]. Cell electrospinning has also been performed, allowing the direct incorporation of live cells during the scaffold manufacturing process [294].…”
Section: Electrospinningmentioning
confidence: 99%
“…Additionally, nutlin-3a induced excessive oxidative stress in cancer cells. Moreover, a secondary apoptotic pathway by nutlin-3a was induced by the overproduction of ROS with irreversible destructive effects on subcellular organelles such as the nucleus and mitochondria [261]. Wang et al also used core–shell-structured polyplex to transfer the fluorescent probe YOYO-1-labeled DNA with high transfection efficacy and low toxicity.…”
Section: Gene Deliverymentioning
confidence: 99%
“…In addition, in some cases, it has been reported that they are able to offer excellent protection against enzymatic degradation or immune attack [28][29][30]. Finally, NPs may contain factors able to down-regulate oncogenes or restore tumor suppressor genes [31][32][33].…”
Section: Introductionmentioning
confidence: 99%